100 Best birdwatching sites In India - Grewal, Bikram and Singh, Bhanu (New Delhi Prakash Books, 2020)
India has a wide diversity of birdlife, comprising more than 1, 300 species, of which 75 are endemic, making the country a richly rewarding destination for birdwatchers. This fully illustrated guide describes the 100 Best sites for reviewing both common and rare species throughout the 26 states of the sub-continent, including the Andaman and Nicobar islands. Alongside a map of each area, detailed descriptions of each site cover the type of terrain and specific spots at which certain species are likely to be encountered. Other sections cover access and possible accommodation, as well as important indicators to conservation issues. A fact file for each site lists the nearest major town; the type of habitat; key species to be seen as well as other wildlife specialities, and the best time to visit.
Keywords: Aves-Birds; Birdwatching sites- India